2023
DOI: 10.3390/polym15061456
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Mechanical Characterization of Unprecedented Transparent Epoxy–Nanomica Composites—New Model Insights for Mechanical Properties

Abstract: Two nanomicas of similar composition, containing muscovite and quartz, but with different particle size distributions, have been used to prepare transparent epoxy nanocomposites. Their homogeneous dispersion, due to the nano-size, was achieved even without being organically modified, and no aggregation of the nanoparticles was observed, thus maximizing the specific interface between matrix and nanofiller. No exfoliation or intercalation has been observed by XRD, despite the significant dispersion of the filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…), nanoclays can be used as environmentally friendly fillers in polymeric materials. Mechanical strength and biodegradability can be improved by adsorbing small amounts of nanoscale clay particles into the polymer matrix [18,93]. Polymer-nanoclay composites are successfully applied in several fields, such as aerospace, automotive, petroleum, biomedical, construction, and wastewater treatment.…”
Section: Nanoclays In Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…), nanoclays can be used as environmentally friendly fillers in polymeric materials. Mechanical strength and biodegradability can be improved by adsorbing small amounts of nanoscale clay particles into the polymer matrix [18,93]. Polymer-nanoclay composites are successfully applied in several fields, such as aerospace, automotive, petroleum, biomedical, construction, and wastewater treatment.…”
Section: Nanoclays In Polymersmentioning
confidence: 99%
“…However, Trinh et al [114] observed that most sustainable polymer alternatives cannot compete with traditional plastics in gas and moisture barrier properties. Recently, improved moisture barrier properties were obtained by the encapsulation of nanoclay platelets into epoxy resin [93,95,106,[115][116][117]. Organically modified montmorillonite is a commonly used nanoclay dispersed in epoxy resins with filling amounts ranging from 1 to 10 wt% [117].…”
Section: Nanoclays In Polymersmentioning
confidence: 99%